PERSEPSI MASYARAKAT TERHADAP PELAYANAN PUBLIK DI KANTOR KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Hari . (Jurnal Paradigma (JP), 2017)
The aim of this research is to understand the public perception toward public service in Kecamatan Office of Samboja. The result emphasizes that public service in Samboja is very well. Relating to responsiveness, empathy, tangibles and assurance the public assume that services were delivered in good kind.